ANALISIS FRAMING PEMBERITAAN MENGENAI ARAB SAUDI PADA MEDIA ONLINE DETIKCOM - Muhammad Fikri Ardiansyah (Bashirah, 2022)
This study examines the problem formulated as follows: “There is negative news about Saudi Arabia in Indonesia. One example is the news about the opening of a Dog Cafe in Saudi Arabia under the name "The Barking Lot", which was reported by detik.com." After tracing the news, it turns out that “The Barking Lot” is not a dog cafe, but a pet care center that also provides a cafe for animal owners who are waiting for their pets to take care of, this can be found on the Official Instagram of “The Barking Lot”. This study aims to determine the framing carried out by detikcom in its coverage of Saudi Arabia. This was done because of an attempt to frame news about Saudi Arabia. The method used in this research is the analysis of the framing model of Robert N. Entman. The data collection technique is to observe news texts about Saudi Arabia on the online media detikcom. The theory used in this research is the social construction of mass media on social reality. Based on the results of the study, it can be concluded that the framing of news about Saudi Arabia published by detikcom is not always the same. This is influenced by the issues, perpetrators, and victims in the published news.